Continuous software engineering—A microservices architecture perspective. Issue 11 (6th April 2017) - O'Connor, Rory V.; Elger, Peter; Clarke, Paul M.
Abstract: From its earliest days, software development has been beset with challenges in relation to timely delivery, appropriateness of features, and quality of deliverables. Many advances in software development processes have helped to address these concerns. For example, agile software development has helped to deliver working software more frequently, and capability maturity frameworks have brought about improved consistency in quality levels. However, the age‐old challenge of better, cheaper, faster software has continued to beguile developers. In this paper, we discuss an emerging approach to software development, continuous software engineering (CSE), wherein software of operational quality may be delivered on a very frequent basis, up to many times in a given day. This approach uses a complex set of independent tools that together reduce the lead time in delivering commercial‐grade software. Having examined the situational context of one industrial organization applying CSE, we conclude that the approach may not presently be appropriate to all manners of software development. Nonetheless, the authors are of the view that CSE represents a significant progression in software engineering and that software development settings of all types stand to gain from aspects of the CSE approach.